Touched by your words: How touch-related vocabulary prompts charitable behavior by reducing the negative effect of disgust - Petit, Olivia (Frontiers in Psychology, 2023)
Getting help is often difficult for people who trigger disgust (e.g., homeless, sick, or disabled people) as well as the charities representing them because of low trust in these groups. Prior research has demonstrated that physical contact can help increase generosity. However, it is difficult to trigger this phenomenon –called Midas Touch Effect– when people feel disgust and are uncomfortable with interpersonal touch. This research examines touch-related vocabulary (e.g., “I would be touched”, “anyone who I can contact”) as an alternative, non-physical way for prompting the Midas Touch Effect. This research examines if such a vocabulary may reduce the negative effects of disgust on trust, and thus increase the willingness to donate. Across two studies, it is shown that while disgust has a negative effect on trust and willingness to donate to a homeless person when no touch-related vocabulary is used, no such negative effect is observed when the message includes touch-related vocabulary.